2020
DOI: 10.1007/s43440-020-00097-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of single and repeated administration of ketamine in unipolar and bipolar depression: a meta-analysis of randomized clinical trials

Abstract: Background Due to unmet clinical needs for efficient drugs with a rapid onset of antidepressant effects, we aimed to evaluate the efficacy of single-dose ketamine in different subgroups of patients with major depression and establish whether repeated ketamine administration could be a viable strategy to maintain treatment gains. Methods Electronic databases (Medline via PubMed, Embase, Cochrane Library, Trip Database) were systematically searched until February 22, 2019, for published peer-reviewed randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 69 publications
2
77
0
Order By: Relevance
“…Interestingly, Vande Voort et al (2016) reported that four subjects lost remission status during the drug free post-continuation phase, but they maintained a MADRS total score not different from that evaluated 24 h after the first acute infusion suggesting an enduring ketamine effect. A recent meta-analysis of 20 randomized and controlled studies evaluated the efficacy of a single or repeated ketamine dose in different subgroups of patients with MDD and bipolar depression (Kryst et al, 2020); the authors reported that a single dose of ketamine, reduced depressive symptoms, producing the largest antidepressant effect at 24 h, however, a significant effect was seen up to 7 days after ketamine administration. In addition, ketamine's effect could be observed in TRD patients, who received ketamine in monotherapy, but also when ketamine was used as adjunctive to the current antidepressant therapy, in both unipolar and bipolar depression.…”
Section: Ketamine's Effects: Single Versus Repeated Administration Gementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Vande Voort et al (2016) reported that four subjects lost remission status during the drug free post-continuation phase, but they maintained a MADRS total score not different from that evaluated 24 h after the first acute infusion suggesting an enduring ketamine effect. A recent meta-analysis of 20 randomized and controlled studies evaluated the efficacy of a single or repeated ketamine dose in different subgroups of patients with MDD and bipolar depression (Kryst et al, 2020); the authors reported that a single dose of ketamine, reduced depressive symptoms, producing the largest antidepressant effect at 24 h, however, a significant effect was seen up to 7 days after ketamine administration. In addition, ketamine's effect could be observed in TRD patients, who received ketamine in monotherapy, but also when ketamine was used as adjunctive to the current antidepressant therapy, in both unipolar and bipolar depression.…”
Section: Ketamine's Effects: Single Versus Repeated Administration Gementioning
confidence: 99%
“…In addition, ketamine's effect could be observed in TRD patients, who received ketamine in monotherapy, but also when ketamine was used as adjunctive to the current antidepressant therapy, in both unipolar and bipolar depression. Several studies evaluated the efficacy of ketamine repeated treatments; importantly, serial ketamine administration (twice or thrice a week for three weeks) produced a significant and sustained antidepressant effect over placebo at three weeks, both in terms of depression symptoms and in terms of remission (Kryst et al, 2020).…”
Section: Ketamine's Effects: Single Versus Repeated Administration Gementioning
confidence: 99%
“…The antidepressant combination treatment with mirtazapine 45 mg and venlafaxine 375 mg was expanded with vortioxetine 10 mg/die, but failed to improve the symptoms. Neither augmentation with second-generation antipsychotics (aripiprazole 20 mg/die) ( 14 ) and S-ketamine ( 15 ) that was administered 2–3 times/week intravenously (up to 50 mg per infusion), nor a series of 11 electroconvulsive therapies (ECT) with subsequent regular maintenance ECTs, all with bilateral stimulation up to 100%, improved the severe depressive symptoms ( 16 ).…”
Section: Case Presentationmentioning
confidence: 99%
“…Numerous early studies had consistently reported that an antagonist of glutamatergic N-methyl-D-aspartate (NMDA) receptors ketamine at subanesthetic doses could result in fast-acting and sustained antidepressant effects in individuals suffering from unipolar and bipolar depression ( Na & Kim, 2021 ; Phillips et al, 2020 ). For example, ketamine’s repeated administration had quick and enduring antidepressant and antisuicidal effects in depressed patients ( Kryst et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%